Evaluation of Differentiated Learning for Students with Special Needs in Inclusive Classes at TK Pembina Kabupaten Kutai Timur - Herni Masseru; Ishartiwi Ishartiwi (Electronic Journal of Education, Social Economics and Technology, 2025)
This study evaluates the implementation of differentiated learning for students with special needs in the inclusive classroom of TK Pembina Kabupaten, focusing on accommodation readiness, teacher understanding, and implementation of differentiation. Using Provus' discrepancy evaluation model, data was collected through observation, interviews, questionnaires and documentation from 15 respondents. The results show that the implementation of differentiated learning is quite good. Physical, media and administrative accommodations are generally available, although mobility and communication aids are still limited. Teachers show good understanding in planning and implementing differentiation in content, process, product and learning environment. The implementation of learning also runs effectively, marked by the adjustment of materials based on students' abilities, interests and learning styles. The learning environment is designed inclusively, supporting the active participation of all students. The findings indicate that differentiated learning has contributed positively to the success of inclusive education in Pembina District kindergarten.